Ameliorative effect of α-tocopherol and tocotrienol-rich palm oil extract on menopause-associated mood disorder in ovariectomized mice - Liang, Gengfan; Kow, Audrey Siew Foong; Lee, Yu-Zhao; Yusof, Rohana; Tham, Chau Ling; Ho, Yu-Chung; Lee, Ming Tatt (Elsevier, 2024)
Menopause-associated mood disorder is characterized by emotional depression, anxiety, and stress, which accompany hypogonadism in women in the menopausal phase. The current treatment for menopause-associated mood disorder provides only symptomatic relief and is associated with many side effects. Supplementation with vitamin E has been shown to be effective in ameliorating anxiety and depression. However, the effects of vitamin E and its underlying mechanism in ameliorating menopause-associated mood disorders remain uncertain. This work evaluated the effects of α-tocopherol and tocotrienol-rich palm oil extract on depressive and anxiety-related phenotypes induced by estrogen deficiency through ovariectomy in mice. Our study revealed that ovariectomized mice exhibited alterations in behavior indicative of depressive- and anxiety-like behaviors. The serum corticosterone level, a glucocorticoid hormone associated with stress, was found to be elevated in ovariectomized mice as compared to the sham group. Oral administration of α-tocopherol (50 and 100 mg/kg) and tocotrienol-rich palm oil extract (100 and 200 mg/kg) for 14 days alleviated these behavioral changes, as observed in open field, social interaction, and tail suspension tests. However, treatment with tocotrienol-rich palm oil extract, but not α-tocopherol, modulated the depressive- and anxiety-like responses in ovariectomized mice subjected to chronic restraint stress. Both treatments suppressed the elevated serum corticosterone level. Our findings suggested that α-tocopherol and tocotrienol-rich palm oil extract alleviated menopause-associated mood disorder, at least in part, by modulating the hypothalamic-pituitary-adrenal (HPA) axis. The findings of this study can provide a new foundation for the treatment of menopause-associated depressive- and anxiety-like phenotypes, for the betterment of psychological wellbeing. © 2024 Elsevier Inc.